Cancer survivors' attitudes towards and knowledge of physical activity, sources of information, and barriers and facilitators of engagement: A qualitative study. (30th January 2017) - Smith, L.; Croker, H.; Fisher, A.; Williams, K.; Wardle, J.; Beeken, R. J.
Abstract : Limited literature exists on attitudes towards, knowledge of and where cancer survivors seek information on physical activity. This study aimed to address these gaps in the literature. Interviews were conducted with 19 UK‐based adult cancer survivors. Interviews covered participants' knowledge of the relationship between physical activity and cancer, sources of information and attitudes towards physical activity following their cancer treatment. Data were analysed using Thematic Analysis. Key themes included "physical activity is good for you, " "desire to be more physically active, " "limited guidance on participation in physical activity, " "multi‐dimensional barriers and facilitators of physical activity." Participants thought physical activity was good for them, and felt they should be more physically active. Participants reported receiving little information from oncology health professionals, as well as a desire for more guidance. Tiredness/fatigue was an important reported barrier to physical activity participation, as were situational constraints. Social support and structured exercise programmes were reported to facilitate physical activity. Health professionals should be encouraged to direct patients to appropriate sources for guidelines on physical activity for cancer survivors. Multi‐component interventions to increase physical activity behaviour that consider tiredness/fatigue and incorporate components of social support could be explored.